The 20th Anniversary of Pharmaceuticals — Multi-Targeted Natural Products as Therapeutics (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue summarizes the latest research findings on identifying natural products targeting multiple pathways and body functions that can successfully treat multifactorial diseases. Research articles presented in this issue may be of great interest to pharmacologists, pharmacists, and physicians interested in the complementary treatment of disease.